Current concepts review. Management of proximal tibial fractures - Gahr, Patrick; Kopf, Sebastian; Pauly, Stephan (Frontiers in Surgery, 2023)
The management of proximal tibial fractures has evolved significantly in recent years. While the main goals of treatment - stability, restoration of the mechanical axis, and smooth articular surfaces - remain the same, methods have advanced substantially. In diagnostics, technical progress in CT and MR imaging has led to a better three-dimensional understanding of the injury. Newly developed classification systems such as the three-column concept of Luo et al. and the 10-segment concept of Krause et al. take this into account. Accordingly, there is a trend towards tailored approaches for particular fracture localizations. Parallel to this development, there is increasing evidence of the advantages of arthroscopically assisted surgical procedures. This Current Concepts article reviews classifications, diagnostics, treatment options as well as complications in fractures of the proximal tibia.